Validation of a post-cracking law in tensile for a sustainable UHPFRC using fracture energy and finite element method - Aguero, Rosangel Rojas; Aguirre, Jose Rafael Yepez; Filho, Américo Campos; Pacheco, Alexandre Rodrigues (International Journal of Advanced Engineering Research and Science, 2022)
Ultra-high performance fiber reinforced concrete (UHPFRC) is an advanced composite material characterized by compressive and tensile strengths above 150MPa and 7MPa, respectively. Initially, an experimental procedure was used to characterize the tensile performance through bending tests, using beams with 1% and 2% content by volume of steel fibers. Three-point bending load arrangement notched prisms were used to determine the contribution of the fibers to reinforcing a cracked section. With that, the (F vs. ω) experimental curves were graphed, and from there, the analytic tensile curves (σ vs. ω) was obtained point by point by application of the inverse analysis procedure proposed by the AFGC. With the analytic curves, the fracture energy was calculated, following a procedure proposed by RILEM. Subsequently, the crack width was transformed into strain using a relationship that involves the characteristic length. The resulting analytical behavior law was used to carry out computational modeling applying the finite element method. Both the finite element method and the fracture energy were used to validate the procedures, comparing experimental and numerical results. Models and experiments showed good agreement and finally was determined the constitutive law for the UHPFRC in tension. It can be concluded from this study, therefore, that the post-cracking tensile behaviour of UHPFRC can be appropriately evaluated and validated through the applied analysis procedure in this research.